Profil Pemahaman Konsep Teorema Pythagoras Siswa Ditinjau dari Kemampuan Matematika - Fani, Sri; Alfisyhara, Alfisyhara; Lefrida, Rita; Pathuddin, Pathuddin (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to describe students' understanding of the concept of the Pythagorean theorem in class VIII of SMP Negeri 3 Banawa in terms of mathematical ability. The method used in this research is triangulation, data was collected through written tests and interviews. The results of this study showed that ST subjects were able to explain the third indicator given by the researcher. Subject SS could not explain the second indicator because the subject did not understand the cardinal directions so that it affected the third indicator, subject SS could not complete it. SR subjects could not explain the three indicators. In conclusion, students with high mathematical abilities can fulfill the indicators in restating concepts and presenting concepts in the form of mathematical representations (images), and some fulfill the indicators in using certain operating procedures in solving Pythagorean theorem problems. Students with moderate mathematical abilities only partially meet the indicators for restating and presenting concepts in the form of mathematical representations, but have not yet met the indicators for using certain operating procedures. Meanwhile, students with low mathematical abilities only partially fulfill the indicators in restating concepts, but do not meet the indicators in presenting concepts in the form of mathematical representations or in using certain operating procedures. Keywords: Concept Understanding, Pythagorean Theorem, Maths Ability.